A novel poly ligand exchanger – Cu(II)-loaded chelating resin for the removal of ammonia-nitrogen in aqueous solutions. Issue 22 (17th November 2017) - Chen, Quanzhou; Zhou, Kanggen; Chen, Yan; Wang, Aihe; Liu, Fang
ABSTRACT: In this paper, a poly ligand exchanger, Cu(II)-loaded chelating resin bearing the functional group of weak iminodiacetate acid was prepared to efficiently remove ammonia from solutions. Batch adsorption equilibrium experiments were conducted under a range of conditions to determine the optimum adsorption conditions. The effects of contact time, pH, resin dosage and temperature on the removal of ammonia by a Cu(II)-loaded resin were determined. The maximum removal efficiency was reached at pH 9.5 at room temperature, 25°C, in 300 min. The maximum ammonia adsorption capacity was found to be 45.66 mg/L. The maximum adsorption capacities decreased with the increasing of solution temperature. Langmuir, Freundlich and Temkin isotherm models were used for fitting the adsorption experimental data without competing ions and the Langmuir isotherm model was proved to be the best-fitting model by comparing the corresponding correlation coefficients ( R 2 ) of the listed models. The effect of competing ions Na + and Ca 2+ on the adsorption of the Cu(II)-loaded resin for ammonia was investigated. The results showed that the existing of competing ions had a negative effect on the ammonia removal. The adsorption capacities decreased with the increasing concentration of competing ions. The Langmuir isotherm model was used to fit the experimental data and proved efficient. The existing of competing ions in solutions was unfavorable for ammonia adsorption and the weakening effect of bivalent Ca 2+ was stronger than the monovalent Na + . The ammonia adsorption capacity was relatively high compared with other ammonia adsorbents and the Cu(II)-loaded resin was an economically feasible and promising technology for ammonia removal.